Governing Kenya
XVII, 323 p. 9 illus.
Keywords: ‘A major contribution to comparative policy analysis highlighting the commonalities and differences that Kenya shares with other nations in theory and practice. Governing Kenya will remain a key text for years to come’. —Michael Howlett, Burnaby Mountain Chair of Political Science, Simon Fraser University, Canada ‘Governing Kenya integrates public policy theory with extensive examples to provide a valuable portrait of this important African country. An invaluable contribution to the literature on public policy in Africa’. —B. Guy Peters, Professor of Comparative Governance, University of Pittsburgh, USA ‘A superb example of development scholarship which sets aside ‘best practice’ nostrums and focuses on governance challenges specific to time and place while holding on to a comparative perspective. Useful to scholars and practitioners across developing areas!’ Brian Levy, Professor, Mandela School of Public Governance, University of Cape Town, South Africa ‘This book on public policy in Kenya gives the reader theoretical and practical hooks critical to the analysis of how the 2010 Constitution is implemented’. —Willy Mutunga, Chief Justice and President of the Supreme Court, Republic of Kenya, 2011-2016. ‘This book is an exploration of important deliberations that help us understand public policy theories and their application within a specific African setting’. —Wilson Muna, Lecturer of Public Policy, Kenyatta University, Nairobi, Kenya This book is authored by renowned scholars in Africa to understand how Kenya is governed. It addresses three pertinent questions: (1) how are policies made where change is demanded, but institutional legacies resist? (2) how are power and authority shared among institutional actors? and, (3) how do increasingly complex policy problems involving multiple stakeholders affect policymaking? It provides an updated and relevant foundation for teaching public policy in Kenya from a comparative perspective while also serving as a useful guide for politicians, government servants, civil society, and businesses on how Kenya is governed. Gedion Onyango is Lecturer, Department of Political Science and Public Administration, University of Nairobi, Kenya. Goran Hyden is Distinguished Professor Emeritus in Political Science at the University of Florida, USA. .